2024
DOI: 10.2118/219472-pa
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Model for Hydrogen Transport and Storage in Shale Reservoirs

Yanwei Wang,
Qian Sun,
Fangxuan Chen
et al.

Abstract: Summary Utilizing underground geological structures for hydrogen storage is an effective approach for energy transformation. The depleted shale reservoirs can be considered as promising options for large-scale hydrogen storage because of the vast storage capacity, high containment security, and low operation cost. However, it is challenging to characterize the hydrogen transportation mechanism and estimate hydrogen storage potential in shale formations from multiscale perspectives. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Under the conditions of 307.15 K and 101.35 kPa, the adsorption capacity of CO 2 reaches 0.577 mmol/g, while that of CH 4 is only 0.186 mmol/g under the same conditions. Therefore, in coal pores, CO 2 has a stronger adsorption capacity than CH 4 , which means that it can displace CH 4 from coal and accelerate CH 4 desorption. The gas adsorption capacity obtained in this study exceeds that reported in the previous literature [34], primarily due to the incorporation of inorganic constituents within the established porous model of anthracite.…”
Section: Interaction Energy and Adsorption Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Under the conditions of 307.15 K and 101.35 kPa, the adsorption capacity of CO 2 reaches 0.577 mmol/g, while that of CH 4 is only 0.186 mmol/g under the same conditions. Therefore, in coal pores, CO 2 has a stronger adsorption capacity than CH 4 , which means that it can displace CH 4 from coal and accelerate CH 4 desorption. The gas adsorption capacity obtained in this study exceeds that reported in the previous literature [34], primarily due to the incorporation of inorganic constituents within the established porous model of anthracite.…”
Section: Interaction Energy and Adsorption Capacitymentioning
confidence: 99%
“…Coalbed methane (CBM) represents a significant non-traditional source of natural gas and contains predominantly CH 4 with small quantities of CO 2 , N 2 , and other gases [1][2][3]. China has rich CBM resources in high-rank coal, with a total resource base of 30.05 trillion cubic meters, but most gas wells have low production, generally at medium and low levels [4]. CO 2 -enhanced coalbed methane recovery (CO 2 -ECBM) has been proven to be an efficient technique for enhancing CBM recovery by taking advantage of the high adsorption capacity of CO 2 to desorb CH 4 without significantly reducing the seam pressure [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…15 coal seam exhibits significant thickness, high adsorption capacity, moderate gas content, low critical desorption pressure, and substantial gas production potential (Jiang et al, 2022). At present, the commercial development of CBM from high-rank coal reservoirs in Qinshui Basin has achieved remarkable results (Nie et al, 2000;Qin et al, 2005;Chen et al, 2015;Wang et al, 2024b).…”
Section: Introductionmentioning
confidence: 99%